2010
DOI: 10.1007/s12272-010-1005-8
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the selective regulation of dopamine D2 and D3 receptors

Abstract: Among the characterized dopamine receptor subtypes, D₂ receptor (D₂R) and D₃ receptor (D₃R) are the main targets of neuroleptics that are currently in use. In particular, D₃R is closely related to the etiology of schizophrenia and drug addiction. The spatial expression patterns of D₂R and D₃R are distinct in certain areas of the brain. D₂R are heavily expressed in the regions responsible for motor functions, whereas D₃R are more selectively expressed in the limbic regions, which are associated with cognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 141 publications
0
60
0
Order By: Relevance
“…Among available atypical antipsychotics, cariprazine is unique in that it has shown almost 10-fold greater affinity for D 3 than D 2 receptors in vitro 28 and high and balanced in vivo occupancy of both D 2 and D 3 receptors. 29,30 The dopamine D 3 receptor is thought to be an important factor in modulating mood and cognition, [31][32][33][34][35] and preclinical evidence suggests that cariprazine may be beneficial in treating negative symptoms, mood dysphoria, and cognitive impairment associated with schizophrenia. 33,[36][37][38][39][40][41] Additionally, short-term clinical trials have suggested that cariprazine is generally well tolerated, with no clinically relevant adverse effects on metabolic parameters, prolactin, or electrocardiogram QT interval.…”
Section: Resultsmentioning
confidence: 99%
“…Among available atypical antipsychotics, cariprazine is unique in that it has shown almost 10-fold greater affinity for D 3 than D 2 receptors in vitro 28 and high and balanced in vivo occupancy of both D 2 and D 3 receptors. 29,30 The dopamine D 3 receptor is thought to be an important factor in modulating mood and cognition, [31][32][33][34][35] and preclinical evidence suggests that cariprazine may be beneficial in treating negative symptoms, mood dysphoria, and cognitive impairment associated with schizophrenia. 33,[36][37][38][39][40][41] Additionally, short-term clinical trials have suggested that cariprazine is generally well tolerated, with no clinically relevant adverse effects on metabolic parameters, prolactin, or electrocardiogram QT interval.…”
Section: Resultsmentioning
confidence: 99%
“…3 The D 3 receptor is also thought to be involved in the modulation of mood and may present a novel target for the treatment of the broad mood symptoms associated with bipolar disorder. [4][5][6] The high and balanced occupancy of cariprazine at both D 2 and D 3 receptors, which is unique to cariprazine, 7 may provide distinct benefits in treating acute and mixed mania.…”
mentioning
confidence: 99%
“…Compared with aripiprazole, cariprazine showed lower affinity for D 2 and higher affinity for D 3 receptors [30]. The dopamine D 3 receptor is thought to play roles in the regulation of cognitive and emotional functions [31]. Cariprazine acts as antagonist with moderate affinity at 5-HT 2A and H 1 receptors, but it has no affinity for muscarinic receptors [30].…”
Section: New Drugs With Familiar Mechanismsmentioning
confidence: 98%